IN VITRO STUDIES OF ULCERATIVE COLITIS : I. REACTIONS OF PATIENTS' SERUM WITH HUMAN FETAL COLON CELLS IN TISSUE CULTURES - Broberger, Ove (The Rockefeller University Press, 1963)
By means of immunofluorescent methods it has been shown that sera from children with ulcerative colitis contain antibodies which react with fetal colon cells in tissue culture. 5 out of 13 sera from patients reacted positively when tested for staining antibodies while 12 sera from healthy individuals yielded negative results. The specificity of the staining reactions was confirmed by inhibition experiments. The staining capacity of various sera was correlated to their hemagglutinating titer when tested against phenol-water extracts of human colon. The presence of blood group substances of the ABO system on fetal colon cells in tissue culture could be demonstrated by application of fluorescent H agglutinins from eel. Cross-inhibition experiments indicated that the H agglutinins stained colon antigens which were different from those reacting with the antibodies of ulcerative colitis sera. The reactivity of cultured fetal colon cells with the antibodies in ulcerative colitis sera was retained for up to 12 days, with optimal staining at 4 to 5 days. Reactivity with H agglutinins was present for a longer period, sometimes more than 20 days. Although antigen could be shown to be present on fetal colon cells in tissue culture, exposure of the culture, in the presence of fresh guinea pig serum, to sera from patients with ulcerative colitis did not lead to any visible cytotoxic damage. In order to investigate the possible cytotoxic effect of the sera with a more sensitive technique, freshly explanted fetal colon was dispersed by trypsinization and the cells labeled with (32)P-orthophosphate. Subsequently, these cells were exposed to sera, in a final concentration of 30 per cent, from patients or healthy controls in the presence of fresh guinea pig serum (final concentration 15 per cent). Approximately 20 per cent of the cellular isotope was released into the medium within 150 minutes of incubation, but the release was the same in the samples treated either with patients' sera or normal control sera. Thus, under the present conditions, the patients' sera did not exert any specific cytotoxic action on colon cells.